Concomitant multiple myeloma, gastric adenocarcinoma and Evan's syndrome in a patient presenting with anaemia. (15th December 2016) - Al-Ammari, Maged; Adam, Soheir
Abstract : An association between multiple myeloma (MM) and solid tumours has been previously described. 1 Furthermore, autoimmune disorders can precede plasma cell dyscrasias, and the pathogenesis of MM maybe linked to chronic immune stimulation. 2 We describe a case of concomitant MM and gastric adenocarcinoma preceded by Evan's syndrome. A previously healthy woman presented to the emergency room with symptomatic anaemia. Her initial workup was compatible with autoimmune haemolytic anaemia and monoclonal gammopathy of undetermined significance. On progression of the anaemia and development of thrombocytopenia, she was diagnosed with Evan's syndrome. Two months later, she presented with severe back pain and her MRI revealed L4–5 vertebral collapse. The clinical picture was compatible with MM. Occult blood was repeatedly positive in stools, and she underwent oesophagogastroduodenoscopy and was found to have gastric adenocarcinoma. The patient refused surgical resection of the adenocarcinoma and refused active treatment for MM.